Gaia GraL: Gaia DR2 gravitational lens systems: VI. spectroscopic confirmation and modeling of quadruply imaged lensed quasars - Stern, Daniel; Djorgovski, S. G.; Krone-Martins, A.; Sluse, D.; Delchambre, L.; Ducourant, C.; Teixeira, R.; Surdej, J.; Boehm, C.; Brok, J. den; Dobie, D.; Drake, A.; et al. (The astrophysical journal, 2021)
Combining the exquisite angular resolution of Gaia with optical light curves and WISE photometry, the Gaia Gravitational Lenses group (GraL) uses machine-learning techniques to identify candidate strongly lensed quasars, and has confirmed over two dozen new strongly lensed quasars from the Gaia Data Release 2. This paper reports on the 12 quadruply imaged quasars identified by this effort to date, which is a ∼20% increase in the total number of confirmed quadruply imaged quasars. We discuss the candidate selection, spectroscopic follow-up, and lens modeling. We also report our spectroscopic failures as an aid for future investigations.
Gesehen am 15.12.2021